Optimized spherical manganese oxide-ferroferric oxide-tin oxide ternary composites as advanced electrode materials for supercapacitors. (18th September 2015) - Zhu, Jian; Tang, Shaochun; Vongehr, Sascha; Xie, Hao; Meng, Xiangkang
Abstract Inexpensive MnO2 is a promising material for supercapacitors (SCs), but its application is limited by poor electrical conductivity and low specific surface area. We design and fabricate hierarchical MnO2-based ternary composite nanostructures showing superior electrochemical performance via doping with electrochemically active Fe3O4 in the interior and electrically conductive SnO2 nanoparticles in the surface layer. Optimization composition results in a MnO2–Fe3O4–SnO2 composite electrode material with 5.9 wt.% Fe3O4 and 5.3 wt.% SnO2, leading to a high specific areal capacitance of 1.12 F cm−2 at a scan rate of 5 mV s−1. This is two to three times the values for MnO2-based binary nanostructures at the same scan rate. The low amount of SnO2 almost doubles the capacitance of porous MnO2–Fe3O4 (before SnO2 addition), which is attributed to an improved conductivity and remaining porosity. In addition, the optimal ternary composite has a good rate capability and an excellent cycling performance with stable capacitance retention of ∼90% after 5000 charge/discharge cycles at 7.5 mA cm−2. All-solid-state SCs are assembled with such electrodes using polyvinyl alcohol/Na2SO4 electrolyte. An integrated device made by connecting two identical SCs in series can power a light-emitting diode indicator for more than 10 min.